Komparasi Rasio Keuangan PT. Aneka Tambang, PT. Adaro, PT. Baramulti Suksessarana Perusahaan Sektor Tambang untuk Menilai Stabilitas dan Pertumbuhan Perusahaan - Kristiana Greta Calosa; Nur Fitroten Dian Sari; Marcella Aulia Jayadi; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze and compare the financial ratios of three mining companies, namely PT Aneka Tambang, PT Adaro Energy, and PT Baramulti Suksessarana, in assessing company stability and growth. The analysis was conducted using a qualitative descriptive approach by utilizing financial ratio data such as liquidity, activity, solvency, profitability, and market in the 2019-2023 period. The results show that PT Aneka Tambang excels in liquidity stability, PT Baramulti Suksessarana has high efficiency in asset utilization, and PT Adaro Energy offers great growth potential with significant fluctuations in profitability. This research provides strategic insights for investors in selecting mining companies according to risk profiles and investment objectives, as well as a reference for academics in understanding the dynamics of the financial performance of the mining sector